2022
DOI: 10.1002/cti2.1398
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17A and interleukin‐22 production by conventional and non‐conventional lymphocytes in three different end‐stage lung diseases

Abstract: Objectives The contribution of adaptive vs. innate lymphocytes to IL‐17A and IL‐22 secretion at the end stage of chronic lung diseases remains largely unexplored. In order to uncover tissue‐ and disease‐specific secretion patterns, we compared production patterns of IL‐17A and IL‐22 in three different human end‐stage lung disease entities. Methods Production of IL‐17A, IL‐22 and associated cytokines was assessed in supernatants of re‐stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(107 reference statements)
1
1
0
Order By: Relevance
“…Associations between decreased neutrophil, IL‐8, and IL‐17A levels suggest CFTR modulators may reduce neutrophilic inflammation and, perhaps neutrophil‐mediated lung damage. These findings agree with a recent study that compared CF, lung emphysema, and pulmonary fibrosis and found that CF lung samples had higher levels of IL‐17A and that this correlated with high microbial colonization 36 . Although IL‐17A is secreted by different lymphocyte populations due to bacterial or nonbacterial stimuli, the overproduction of IL‐17A observed in CF appears to be aggravated by increased microbial load, which accelerates end‐stage disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Associations between decreased neutrophil, IL‐8, and IL‐17A levels suggest CFTR modulators may reduce neutrophilic inflammation and, perhaps neutrophil‐mediated lung damage. These findings agree with a recent study that compared CF, lung emphysema, and pulmonary fibrosis and found that CF lung samples had higher levels of IL‐17A and that this correlated with high microbial colonization 36 . Although IL‐17A is secreted by different lymphocyte populations due to bacterial or nonbacterial stimuli, the overproduction of IL‐17A observed in CF appears to be aggravated by increased microbial load, which accelerates end‐stage disease.…”
Section: Discussionsupporting
confidence: 91%
“…These findings agree with a recent study that compared CF, lung emphysema, and pulmonary fibrosis and found that CF lung samples had higher levels of IL-17A and that this correlated with high microbial colonization. 36 Although IL-17A is secreted by different lymphocyte populations due to bacterial or nonbacterial stimuli, the overproduction of IL-17A observed in CF appears to be aggravated by increased microbial load, which accelerates end-stage disease. In contrast, IL-10 remained elevated in pwCF pre-and post-ETI, suggesting continued stimuli from myeloid-and lymphoid-derived immune cells in response to pathogens or other inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%